Influence of Ortho Primer Morelli adhesion booster on orthodontic brackets shear bond strength - Sabrina de Mendonça Invernici; Ivan Toshio Maruo; Elisa Souza Camargo; Thais Miyuki Hirata; Hiroshi Maruo; Odilon Guariza Filho; Orlando Tanaka (Dental Press Editora, 2012)
OBJECTIVE: This work aimed at assessing the bond strength (AS), the site of the flaw and the relation between them and Ortho Primer Morelli® (OPM) adhesion optimizer. METHODS: Sixty test specimens, made out of bovine permanent lower incisors, were divided into three groups: TXT Primer (control), in which a conventional adhesive system was applied (primer and paste); OPM, in which TXT primer was replaced by OPM; and TXT without Primer, in which only TXT paste was used. A shear force was applied at a speed of 0,5 mm/min. Failure site was assessed by the Remaining Adhesion Index (RAI). RESULTS: Kruskal-Wallis demonstrated that OPM (8.54 ± 1.86 MPa) presented a statistically higher AS (p < 0.05) IF compared to TXT Primer (6.83 ± 2.05 MPa). There was no statistically significant difference (p > 0.05) between TXT with or without Primer (6.42 ± 2.12 MPa). Regarding the RAI, the K test demonstrated that TXT Primer and OPM (prevailing scores 2 and 3) showed higher values (p < 0.05) IF compared to TXT without Primer (prevailing scores 0 and 1). Spearman demonstrated that there was no correlation between AS and RAI (p > 0.05). CONCLUSION: OPM increases AS and presents the same bond failure location if compared to a conventional adhesive system; the use of the TXT adhesive system paste only was shown to have the same AS if compared to conventional systems, except it does not allow to predict the adhesive failure site; there is no correlation between AS and bond failure location, regardless of the use of any adhesion optimizer.